THE EFFECT OF WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT THE CURIO DISTRICT OFFICE, ENREKANG REGENCY - Rasmawati, Rasmawati; Amin, Andi Mustika; Burhanuddin, Burhanuddin (Universitas Negeri Makassar, 2026)
Abstract: This study aims to determine the effect of work motivation on employee performance at the Curio District Office, Enrekang Regency. This study used a quantitative approach with 30 respondents who were employees at the Curio District Office. Data were collected through questionnaires and analyzed using simple linear regression with the help of the SPSS program. The results showed that the level of work motivation of respondents was in the high category (93.3%), while employee performance was in the medium to high category (50% each). The regression test showed that work motivation had a positive effect on employee performance with a regression coefficient of 0.333. The t-test showed a significance value of 0.001 <0.05, which means that work motivation had a significant effect on employee performance. Thus, the alternative hypothesis (Ha) was accepted and the null hypothesis (H₀) rejecte.Keywords: Motivation, Performance.